Computational re-design of Streptomyces griseus Chitinase C and analysis of biochemical, biophysical and antifungal properties of designed variants - Omolola, Oyeleye Ayokunmi (2021)
Despite the importance of chitinases as potential biocontrol agents, their applications have not attracted significant attention due to the lack of stable enzyme formulations, high production costs and low yields from both wild and recombinant sources. However, through protein engineering techniques, these limitations can be overcome. Engineered mini-proteins for instance, could possess; enhanced stability, low production costs and simplified structural and functional mechanisms. Thus, this study was focused on developing miniaturized variants of Streptomyces griseus HUT6037 chitinase C that could serve as simpler yet potentially stable antifungal agents. Through computational techniques involving sequence analysis, docking and molecular dynamics simulation important residues and/or motifs within the catalytic cleft of SgChiC were identified as essential for recognition and binding to complex or crystalline chitin. Residues outside the catalytic clefts were thus considered targets for miniaturization. Five (5) SgChiC variants namely: M159, M140, M139, M109 and M101 were designed in silico, their genes were subsequently synthesised and cloned into pET-22b(+). The variants were then expressed in Escherichia coli BL21(DE3) and purified through on-column refolding. Biochemical assays revealed that all variants although had lower activities towards colloidal chitin when compared with the wild-type, retained the optimum temperature at 40 C. The optimum pH for activities of variants however varied with M101 and M139 drifting towards acidic pH of 5.0 and 6.0 respectively, while M159 and M109 had optimum activities at pH 8. Interestingly, all variants retained 40-50% of the specific activity of the WT towards colloidal chitin, with M159 displaying the highest specific activity at 31.6 Umg-1 compared to the WT with 52.3 Umg-1. Contrastingly, with chitosan, the smallest variant M101, displayed high chitosanase activity comparable with the WT with 59.6 and 61.4 Umg-1 respectively. M109 also displayed high chitosanase activity with a specific activity of 51.6 U/mg. Thermal denaturation studies revealed that the variants were stable at temperatures up to 60°C. Antifungal assay towards Fusarium oxysporum f.sp. cubense (FOC) revealed that M101 and M109 had the capacity to inhibit hyphal extension against the fungus with M101 displaying comparable inhibition with the WT. M139, M140 and M159 exhibited less inhibitory effects towards the hyphal extension of FOC. Finally, a correlation between chitosanase and antifungal activities of the enzymes was observed in the study whereby only the wild type and variants with chitosanase activities clearly inhibited fungal growth. The computational approach applied in the engineering of SgChiC was therefore efficient as it yielded miniaturized variants that may be beneficial in the study of chitinases and their mechanisms. Additionally, the variants, especially M101 which exhibited some activities comparable with the wild-type can be further improved in future studies as antifungal formulation.